DETERMINATION OF DEOXYGENATION RATE OF URBAN RIVER USING MODIFICATION METHODS FOR CITEPUS RIVER WATER, BANDUNG, INDONESIA - Yonik Meilawati Yustiani; Mia Nurkanti; Fadhlan Khusyairi Tarigan; Gatut Sudarjanto (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
River water quality modeling needs appropriate and suitable coefficients especially in application for specific river like urban river. Aim: This study aims to determine the value of the coefficient with a short term duration and a variable test time span.  Several ways and methods of determining the rate of deoxygenation are developed according to the characteristics of the river and the environment. Modification method was applied in this research in which the test time span was unequal. The river chosen in this study is the Citepus River, Bandung, Indonesia representing an urban river in a tropical country. Methodology and Results: Sampling was carried out in the dry season. The laboratory analysis method used in determining the rate of deoxygenation uses the Slope Method of data from the short term incubation, which is ten days. The results showed that the Thomas Slope method's deoxygenation rate (K1) was 0.095 per day in the upstream segment, 0.917 per day in the middle segment, and 0.180 per day in the downstream segment. While the Ultimate BOD (La) value is 46.95 mg/l in the upstream segment, 38.70 mg/l in the middle segment, and 37.60 mg/l in the downstream segment. Conclusion, significance, and impact of study: The results of this study show that the value of the deoxygenation rate is similar to the theoretical surface water conditions. However, in the upstream segment, there is still a low deoxygenation rate value due to non-optimal activity of microorganisms. This findings will be very useful both in water quality modeling and river management.